Meningkatkan Motivasi dan Hasil Belajar dengan Menggunakan Metode Diskusi pada Mata Pelajaran Matematika Materi Persamaan Linier Dua Variabel Di Kelas VIII-B SMP Negeri 1 Grogol Kabupaten Kediri - Sujoko, Nanang Andi (Jurnal Simki Postgraduate, 2022)
The purpose of this study was to increase motivation and learning outcomes by using the discussion method in the mathematics subject matter of two-variable linear equations in class VIII-B of SMP Negeri 1 Grogol, Kediri Regency. This is because students' understanding of the material presented is lacking, the teacher must be active in providing variations in learning, so that students do not become bored so that blocking of the material occurs. Students should have space to convey their thoughts so that boredom does not occur at every meeting in learning. The most appropriate method is discussion because here students are taught how to think critically. There is at least two-way communication when applying the discussion method. The discussion method is an appropriate learning method to improve the quality of interaction between students. The goal is to gain a clearer and more thorough shared understanding of something, as well as to prepare and finalize joint decisions. The results showed that there was an increase in student motivation by (0.94) in cycle 1, from 2.56 to 3.5 in cycle 2. In increasing learning outcomes the number of students who were declared to have met KKM standards in cycle 1 were 22 students (62 .86%), and students who met the KKM standards in cycle 2 were 31 students (88.57%). The percentage increase was 25.71% from cycle 1. So it can be concluded that the application of the discussion method can increase the motivation and learning outcomes of class VIII-B UPTD SMP Negeri 1 Grogol material on Linear Equations of Two Variables. So it can be concluded that the discussion method can increase the motivation and learning outcomes of class VIII-B UPTD SMP Negeri 1 Grogol in the matter of Linear Equations of Two Variables.